TEACHING METHODS THAT IMPROVE THE DEGREE OF READABILITY OF EDUCATIONAL MATERIALS (Scientific journal of the Fergana State University, 2023)
The article shows the interest of students in the educational material, understanding the content of the fiction, independent conclusions, increasing the motivation